The Effect Of Macroeconomic Factor On Stock Return Of Pt Unilever Indonesia Tbk - Rahman, Haikal; Rizal, Nora Amelda; Kusairi, Suhal (eProceedings of Management, 2023)
The indicators of the successful economy is macroeconomic performance. This macroeconomic factors can affectactivities of industry, company and the capital market as well. In 2016-2021, economic growth of all over the worldhas a severe decline, especially in 2019 due to the emergence of the Covid 19 pandemic, one of the sectors that hasexperienced fluctuations is the consumer goods sector, PT Unilever Indonesia is one of the consumer goods sectorcompany that experienced the unusual fluctuate of their company stocks price.This research aims to analyze theimpact of macroeconomic variable such as inflation, interest rates and exchange rates toward the return of acompany's stock. The sample used in this study are data from PT Unilever Indonesia Tbk since periods 2016-2021.The method analysis is the quantitative method by using descriptive and the multiple linear regression analysis.Theresults show that simultaneously the variables inflation, interest rates and exchange rates have an effect on PTUnilever Indonesia Tbk return, partially inflation have an effect on stock returns, while interest rates and exchangerates have no significant effect on stock returns partially, Implication of these findings, investors can utilize thisresearch as a reference for further research using other variables that can influence the return of a company's sharesand also use different objects.Keywords-Macroeconomic Indicators, Stocks Return, Inflation, Interest Rates, Exchange Rates.